Sulfur-alkali double-activated solid waste-based cementing material, product and preparation method thereof

By using technical means of sulfur-alkali dual-excitation solid waste-based gelling materials in fluorogypsum-based gelling materials, the problem of poor water resistance and strength of fluorogypsum-based gelling materials is solved, high water resistance and high strength gelling performance is achieved, and the comprehensive utilization path of fluorogypsum is broadened.

CN119504215APending Publication Date: 2025-02-25HENAN POLYTECHNIC UNIV

Patent Information

Application Number
CN202411476443.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The water resistance and/or strength of existing fluorogypsum-based gelling materials lead to limited application in humid environments.

Method used

Sulfur-alkali dual-excitation solid waste-based gelling materials, including fluorine gypsum, low-calcium fly ash and slag powder, are used as gelling substrates, and alkaline materials and composite exciters (such as sodium sulfate and sodium silicate) are added to regulate the hydration process.

Benefits of technology

By regulating the generation rate of hydration products, a double-supported framework structure mainly composed of "dihydrate gypsum - C-(A)-S-H gel and Aft", significantly improving the 28d compressive strength and water resistance of the gelled material, reaching the 42.5 cement strength standard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504215A_ABST
    Figure CN119504215A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur-alkali double-activated solid waste-based cementing material, a product and a preparation method of the sulfur-alkali double-activated solid waste-based cementing material. The sulfur-alkali double-activated solid waste-based cementing material comprises a cementing base material and an additive, the gelling base material is prepared from the following components in percentage by mass: 60 to 70 percent of fluorgypsum, 15 to 25 percent of low-calcium fly ash and 15 to 25 percent of slag powder; the additive comprises an alkaline material and a composite activator, the dosage of the alkaline material is 1%-3% of the mass of the fluorgypsum, and the dosage of the composite activator is 0.5%-3% of the total mass of the gelling base material. According to the sulfur-alkali double-activated solid waste-based cementing material disclosed by the invention, the hydration rates of different types of hydration products can be regulated and controlled in a hydration process to form a double-support framework structure mainly comprising dihydrate gypsum-C-(A)-S-H gel and Aft, so that the 28d compressive strength of the sulfur-alkali double-activated solid waste-based cementing material disclosed by the invention even can reach a 42.5 cement strength standard; the water resistance is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cementitious materials, and in particular relates to a sulfur-alkali dual-excitation solid waste-based cementitious material, a product and a preparation method thereof. Background Art

[0002] Fluorogypsum is a kind of industrial by-product gypsum, which is a toxic and hazardous industrial solid waste. It is a by-product of the fluoride salt plant using fluorite (CaF2) and concentrated sulfuric acid (H2SO4) to produce hydrofluoric acid. Its main chemical composition is type II anhydrous calcium sulfate (type II CaSO4), which is grayish white powder and microcrystalline crystals, and some of them are in block or spherical shape. It contains a certain amount of residual calcium fluoride, sulfuric acid, hydrofluoric acid, a small amount of silicon dioxide and trace amounts of Na + , K + Impurities such as fluorine. Theoretically, 3.6 tons of fluorine gypsum will be produced for every ton of hydrofluoric acid produced. According to relevant statistics, China ranks first in the world in the production of fluorine gypsum waste residue, with an annual production of more than 10 million tons. Since hydrofluoric acid products contain a small amount of slowly reacting CaF2, H2SO4 and hydrogen fluoride, fluorine gypsum is usually acidic. With the development of my country's industry, long-term stacking of fluorine gypsum occupies a large amount of land resources, and the acidic leaching liquid may pollute the surrounding ecological environment.

[0003] Fluorogypsum is an industrial solid waste. Studies have shown that fluorogypsum has similar mineral compositions to natural anhydrite. Both are insoluble anhydrous gypsums. The hydration mechanisms and hydration activities of the two are also similar, which provides the necessary conditions for fluorogypsum to be a potential alternative resource for natural anhydrite. It can react chemically with other mineral materials to produce gelling properties and become a green gelling material. Although it has potential hydration activity, the hydration rate is slow, and activators must be added to modify the fluorogypsum. The low activity and extremely slow hydration and hardening of fluorogypsum are important reasons that limit its development and utilization.

[0004] At present, there are some cases of using fluorinated gypsum to prepare green cementitious materials, but the fluorinated gypsum content is low, accounting for less than 50% of the total cementitious material mass ratio. Especially in humid environments, the application of gypsum-based materials is greatly restricted.

[0005] Fluorogypsum-based materials are currently mostly used in coating production, and the application environment is mostly normal temperature and general humidity, which is not suitable for large-scale use as cementitious materials. CN118324481A discloses a highly water-resistant gypsum-based cementitious material and a preparation method thereof. Under the combined action of modified silicon oxide and CSH, the water resistance coefficient of the cementitious material is improved, and the increase from 7d to 28d is 154%, but its 28d final strength is only about 17.3MPa, and the final strength is not ideal.

[0006] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0007] The object of the present invention is to provide a sulfur-alkali dual-activated solid waste-based cementitious material, a product and a preparation method thereof, so as to solve or improve the problem that the fluorinated gypsum-based cementitious materials in the prior art have poor water resistance and / or strength and are limited in their application in humid environments.

[0008] In order to achieve the above-mentioned purpose, the present invention provides the following technical scheme: a sulfur-alkali dual-activated solid waste-based cementitious material, wherein the sulfur-alkali dual-activated solid waste-based cementitious material comprises a cementitious base material and an admixture; in terms of mass percentage, the cementitious base material comprises: 60%-70% fluorgypsum, 15%-25% low-calcium fly ash and 15%-25% slag powder; the admixture comprises an alkaline material and a composite activator, the amount of the alkaline material is 1%-3% of the mass of the fluorgypsum, and the amount of the composite activator is 0.5%-3% of the total mass of the cementitious base material; the composite activator comprises sodium sulfate and / or sodium silicate.

[0009] Preferably, the alkaline material is calcium oxide and / or carbide slag, and the amount of the alkaline material is 1.2%-2.5% of the mass of the fluorgypsum.

[0010] Preferably, the composite activator is composed of sodium sulfate and sodium silicate, the amount of the composite activator is 1.8%-3% of the total mass of the gelling substrate, and the mass ratio of the sodium silicate to sodium sulfate is 1:3-2:1.

[0011] Preferably, the mass ratio of the low-calcium fly ash to the slag powder is 0.6-1.3.

[0012] Preferably, the mass ratio of the low-calcium fly ash to slag powder is 0.6-1.

[0013] Preferably, the cementitious base material comprises, by mass percentage, 60% fluorgypsum, 15% low-calcium fly ash and 25% slag powder; the admixture comprises an alkaline material and a composite activator, the amount of the alkaline material is 1.2% of the mass of the fluorgypsum, the amount of the composite activator is 1.8%-2% of the total mass of the cementitious base material, and the composite activator is sodium sulfate and / or sodium silicate.

[0014] The present invention also provides a sulfur-alkali dual-excitation solid waste-based product, which adopts the following technical scheme: a sulfur-alkali dual-excitation solid waste-based product, the raw materials of which include the sulfur-alkali dual-excitation solid waste-based cementitious material as described above and water; the mass ratio of water to the sulfur-alkali dual-excitation solid waste-based cementitious material is 0.35-0.45.

[0015] The present invention also provides a method for preparing the above-mentioned sulfur-alkali dual-stimulation solid waste-based product, which adopts the following technical scheme: the preparation method of the above-mentioned sulfur-alkali dual-stimulation solid waste-based product comprises the following steps: S1, weighing water, mixing at least part of the water with a composite stimulator to fully dissolve the composite stimulator, and obtaining a composite stimulator solution; S2, weighing the fluorgypsum, low-calcium fly ash, slag powder and alkaline material in proportion, pouring them into a mortar mixer, stirring and mixing them evenly, and obtaining a mixed dry material; S3, adding the composite stimulator solution and water obtained in step S1 to the mixed dry material, stirring and stirring them evenly, and obtaining a mixed slurry; S4, pouring the mixed slurry into a mold, fully vibrating and compacting it, and putting it into a cement mortar standard curing box for curing after molding and demolding, so as to obtain the sulfur-alkali dual-stimulation solid waste-based product.

[0016] Preferably, in step S4, the curing temperature is 20°C±1°C, and the curing humidity is ≥95%.

[0017] Beneficial effects:

[0018] The sulfur-alkali dual-activated solid waste-based cementitious material of the present invention can adjust the hydration rates of different types of hydration products during the hydration process by selecting the types and amounts of raw materials, and fully utilizes the S, Si and Al components in the raw materials to form a dual-support skeleton structure mainly composed of "dihydrate gypsum-C-(A)-SH gel and Aft". The two structures are cross-linked with each other, so that the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention can even reach the 42.5 cement strength standard at 28d and has the characteristic of high water resistance; while expanding the utilization methods of fluorinated gypsum, it still shows excellent mechanical properties under continuous high humidity maintenance. At the same time, with the increase of high humidity maintenance time, the strength and water resistance are continuously improved, which greatly enhances the gelling properties and water resistance of fluorinated gypsum, improves its mechanical strength, and broadens new ways for the comprehensive utilization of fluorinated gypsum.

[0019] The strength and water resistance coefficient of the sulfur-alkali dual-excitation solid waste-based cementitious material of the present invention can continue to develop under high humidity environments, taking into account the advantages of good water resistance and high strength, which helps to solve the problems of large-scale accumulation, insufficient utilization, low strength, poor water hardness and limited applicable environment of fluorinated gypsum; and the components of the cementitious base material of the sulfur-alkali dual-excitation solid waste-based cementitious material of the present invention are all solid wastes, which is in line with green development and national sustainable development strategies.

[0020] Among the main raw materials in the sulfur-alkali dual-excitation solid waste-based cementitious material of the present invention, fluorgypsum is well-known for its high acidity, resulting in a low overall utilization rate of less than 30%, and long-term storage has great harm to the environment; fly ash is an industrial by-product of power plants. Like fluorgypsum, large amounts of stored fly ash also cause serious space problems, potential risks of air pollution, and water source pollution due to leaching; slag powder is an industrial by-product of steel mills; the present invention uses fluorgypsum, fly ash and slag as the cementitious base materials of the cementitious material of the present invention. All three are industrial solid wastes, but in the cementitious material system of the present invention, they all show excellent strength and water resistance at all ages, achieving efficient utilization of fluorgypsum, low-calcium fly ash and slag powder, and effectively reducing the cost of raw materials, with good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0022] Figure 1 It is a comparison chart of the effect of the mass ratio of low-calcium fly ash to slag powder in the cementitious base material on the strength at 7 days and 28 days;

[0023] Figure 2 It is a comparison chart of the effect of the mass ratio of low-calcium fly ash to slag powder in the cementitious base material on the softening coefficient at the age of 7 days and 28 days;

[0024] Figure 3 This is a high-magnification (5000×) scanning electron microscope image of the hydration product of the sulfur-alkali dual-activated solid waste-based product of Example 3 after curing for 7 days.

[0025] Figure 4 This is a high-magnification (5000×) scanning electron microscope image of the hydration product of the sulfur-alkali dual-activated solid waste-based product of Example 3 after curing for 28 days. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0027] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0028] The present invention aims to solve the problems that the current fluorgypsum-based cementitious materials have poor water resistance and / or poor strength and are limited in application in humid environments, and provides a sulfur-alkali dual-activated solid waste-based cementitious material.

[0029] The sulfur-alkali dual-excitation solid waste-based cementitious material of the embodiment of the present invention includes a cementitious base material and an admixture; in terms of mass percentage, the cementitious base material includes: 60%-70% (for example, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%) of fluorinated gypsum, 15%-25% (for example, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%) of low-calcium fly ash; low-calcium fly ash refers to Class II F fly ash classified according to GB / T1596-2017) and 15%-25% (for example, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%) of slag powder. 20%, 21%, 22%, 23%, 24%); the admixture includes an alkaline material and a composite activator, the amount of the alkaline material is 1%-3% (for example, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2.0%, 2.5%) of the mass of the fluorinated gypsum, and the amount of the composite activator is 0.5%-3% (for example, 1.0%, 1.5%, 2.0%, 2.5%) of the total mass of the cementitious base material; the composite activator includes at least one of sodium sulfate and / or sodium silicate (that is, the composite activator is any one of sodium sulfate or sodium silicate; or, the composite activator is a mixture of sodium sulfate and sodium silicate).

[0030] Fluorogypsum is anhydrous gypsum, which is acidic in nature. There are impurities such as phosphorus and fluorine on its surface. The system density of its single hydration is low, and the hydration product - dihydrate gypsum generated by hydration is not tightly cross-linked. In addition, dihydrate gypsum itself is also slightly soluble in water, resulting in poor hydration activity, low strength after hydration, and poor water resistance. In the prior art, activators are used to activate the activity of fluorogypsum monomers, and the maximum strength is about 30MPa, and the softening coefficient is about 0.7, which is still a long way from the softening coefficient of water-resistant cementitious materials specified in the national standard of more than 0.85. In addition, the activator used is a mixture of sodium nitrite and sodium sulfate, and sodium nitrite is impossible to be used for large-scale utilization and production.

[0031] There are also technical solutions disclosed in the prior art that combine fluorinated gypsum with other cementitious materials to improve the performance of fluorinated gypsum-based cementitious materials. However, most of the related technical solutions disclosed in the prior art consider generating enough gel in the early stage, and are extremely distrustful of dihydrate gypsum. However, if a large amount of CSH gel and Aft are generated in the early stage, and the speed of hydration to generate CSH gel and Aft is too fast, they will cover the surface of unhydrated fluorinated gypsum, making it difficult for fluorinated gypsum to hydrate, making the system of fluorinated gypsum-based cementitious materials not dense, and being eroded by water in a high-humidity environment, the strength cannot be developed, and the fluorinated gypsum-based composite cementitious materials will have poor performance throughout the entire age period or weak development in the later stage. There are also technical solutions disclosed in the literature that make fluorinated gypsum hydrate too quickly, and other cementitious materials at the same stage are difficult to hydrate to generate CSH gel and Aft, so the CSH gel and Aft generated later will break the original structure.

[0032] Based on the above findings, in the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention, slag powder and low-calcium fly ash (LCFA) both contain rich Si and Al components, and the Ca provided by fluorinated gypsum 2+ With SO4 2- , so that the composition of the early hydration products changes from a single dihydrate gypsum to dihydrate gypsum - C-(A)-SH gel and Aft, and the low-calcium fly ash (LCFA) in the later stage is continuously hydrated, ensuring the continuous development of the later performance.

[0033] Specifically: Fluorogypsum and alkaline materials dissolve under activator and alkaline conditions to provide a large amount of Ca 2+ With SO4 2- and OH - ; The alkaline material reacts with the soluble F- in the fluorgypsum to solidify the impurities into CaF2. 2+ With SO4 2-After saturation, it slowly crystallizes to form dihydrate gypsum. With the progress of hydration reaction and the continuous dissolution of alkaline materials, the alkalinity in the slurry becomes higher and higher (in the early stage, fluorinated gypsum is first dissolved under the stimulation of sodium sulfate. As calcium ions and sulfate ions reach saturation, they begin to crystallize to form dihydrate gypsum. After 5 hours of reaction, the system moves to the product side with the hydration reaction. The change in calcium ion concentration promotes the continuous dissolution of calcium hydroxide, and the alkalinity of the slurry continues to rise. The slag quickly dissociates under the activation of sodium silicate. The silicon phase and aluminum phase provided by the calcium ions and slag are hydrated to form C-(A)-SH gel, and continue to react in a sulfate environment to form Aft). The slag powder depolymerizes under alkaline conditions, and the Si-O-Si bond and the Al-O bond are broken to provide silicon phase and aluminum phase. Under the action of the composite activator, these two materials generate a large amount of dihydrate gypsum, C-(A)-SH gel and Aft in the early stage, which ensures the density, strength and softening coefficient in the early stage (under alkaline conditions, slag and fly ash are continuously dissolved, and the Aft and C-(A)-SH generated by the reaction with dihydrate gypsum fill the pores of unhydrated dihydrate gypsum crystals, while refining the pore structure, protecting the dihydrate gypsum from water erosion. At the same time, Aft and C-(A)-SH gel have extremely low solubility in water, and they wrap the undissolved dihydrate gypsum crystals. , forming a double-support interpenetrating skeleton structure mainly composed of "dihydrate gypsum-C-(A)-SH gel and Aft", which hinders the direct contact between water molecules and dihydrate gypsum crystals. The hydration products become richer, the overlap is denser, and the strength and water resistance coefficient and other properties are excellent and continuously improved throughout the entire age period). Low-calcium fly ash is mainly responsible for the stability of the later system in the present invention. Its hydration is very slow. In the early stage, its particle fineness increases the early density. In the later stage, it continuously hydrates and consumes calcium hydroxide to generate Aft and C-(A)-SH gel. The continuous development of the later strength and softening coefficient is proved, and the effect of high strength and high water resistance at all ages is achieved. The sodium silicate in the activator is mainly used to activate the mineral powder and low calcium fly ash (LCFA), and the sodium sulfate is mainly used to activate the fluorinated gypsum. The alkaline material in the present invention not only acts as an alkaline material, provides alkalinity, and neutralizes the impurities on the surface of the fluorinated gypsum (calcium oxide reacts with water to form calcium hydroxide, and calcium hydroxide reacts with HF in the fluorinated gypsum to form CaF2 and water), so that it can be quickly hydrated. The alkaline material can also act on the slag powder, and calcium oxide reacts with water to form Calcium hydroxide can accelerate the early activation of slag powder, making it generate more gel, and at the same time increase the reaction rate of the two, laying a good foundation. However, the amount of alkaline material / sodium sulfate / sodium silicate used is not the more the better. Excessive alkaline material (calcium oxide) will cause gel hydration products to adhere to the surface of calcium hydroxide to form a shell, which is not conducive to its dissolution, preventing it from further participating in the reaction, and having a slow release effect, reducing the hydration rate of slag, resulting in insufficient generation of gel substances, and the system develops slowly in a high humidity environment, which is not conducive to the performance of the whole age.At the same time, excessive sodium sulfate and sodium silicate will cause alkali efflorescence in the system in the later stage, reduce the stability of Aft, reduce the stability of later strength, and cause strength reduction.

[0034] That is, the selection of the components and their amounts in the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention enables the slag powder and fluorinated gypsum to be synchronously hydrated in the early stage to generate Aft, C-(A)-SH gel (mainly derived from the hydration of slag powder) and dihydrate gypsum (derived from the hydration of fluorinated gypsum) under the stimulation of alkaline materials and composite activators. The initial skeleton composed of them ensures the early performance, and the slow hydration of low-calcium fly ash (LCFA) provides a stable and growing later performance, thus realizing a dual-support interpenetrating skeleton structure mainly composed of "dihydrate gypsum-C-(A)-SH gel and Aft", providing high performance at all ages.

[0035] In the hydration process of the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention, the dihydrate gypsum generated by the hydration of fluorinated gypsum as the first hydration product skeleton can also contribute to the system density, softening coefficient and strength. Therefore, the present invention believes that the Ca dissolved in the fluorinated gypsum 2+ With SO4 2- On the one hand, it hydrates into dihydrate gypsum, and on the other hand, the dissolved SO4 2- It can react with the aluminum phase of slag to generate Aft, which provides assistance for the skeleton of the second hydration product. Through reasonable rate regulation of different hydration products, the two can almost simultaneously generate Aft, C-(A)-SH gel and dihydrate gypsum, forming a double-support interpenetrating skeleton structure, so as to lay a good foundation in the early stage, achieve stable performance development in the later stage, and replace cement in some scenarios. It is truly possible to use fluorinated gypsum to turn waste into treasure. It is not simply using highly active substances to support the weak with the strong, and using fluorinated gypsum as a supplementary material in the system, but through sulfates (fluorinated gypsum and sodium sulfate) and alkaline activators (alkaline materials, sodium silicate and sodium sulfate) to regulate the generation rate of different hydration products, so as to achieve high performance at all ages.

[0036] In a preferred embodiment of the sulfur-alkali dual-excitation solid waste-based cementitious material of the present invention, the alkaline material is calcium oxide and / or carbide slag.

[0037] In a preferred embodiment of the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention, the alkaline material is calcium oxide, and the amount of calcium oxide used is 1.2%-2.5% (for example, 1.2%, 1.5%, 1.8%, 2.1%, 2.3% or 2.5%) of the mass of fluorgypsum.

[0038] In a preferred embodiment of the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention, the composite activator is composed of sodium sulfate and sodium silicate, and the amount of the composite activator is 1.8%-3% (for example, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%) of the total mass of the cementitious substrate, and the mass ratio of sodium silicate to sodium sulfate is 1:3-2:1 (for example, 1:3, 1:2.5, 1:2, 1:1.5, 1:1, 1.5:1 or 2:1). Among them, the ratio of sodium sulfate to sodium silicate determines the hydration rate of different substances in the system, which in turn affects the ratio and composite state of each component in the hydration product (for example, the cross-linking state of dihydrate gypsum, Aft and C-(A)-SH gel), and then affects the performance (strength, water resistance) of the hydration product; specifically, if there is too much sodium silicate, it will cause excessive generation of Aft and CSH, affecting the generation rate of dihydrate gypsum; if there is too much sodium sulfate, it will cause excessive generation of dihydrate gypsum, affecting water resistance.

[0039] In a preferred embodiment of the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention, the mass ratio of low-calcium fly ash to slag powder is 0.6-1.3 (for example, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or 1.3). Among them, when the mass ratio of low-calcium fly ash to slag powder is 0.6-1.3, it is helpful to prepare a product with a 28d softening coefficient greater than 0.85, and better water resistance.

[0040] Preferably, the mass ratio of low-calcium fly ash to slag powder is 0.6-1 (especially when the mass percentage of fluorgypsum in the cementitious base material is 60%). When the mass ratio of low-calcium fly ash to slag powder is 0.6-1, it is easier to prepare a product with a softening coefficient greater than 0.85 and high compressive strength.

[0041] In a preferred embodiment of the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention, the cementitious base material comprises, by mass percentage: 60%-65% (for example, 60%, 61%, 62%, 63%, 64% or 65%) of fluorinated gypsum, 20% of low-calcium fly ash and 20%-25% (for example, 20%, 21%, 22%, 23%, 24% or 25%) of slag powder; the admixture comprises an alkaline material and a composite activator, the amount of the alkaline material is 1.2%-3% (for example, 1.2%, 1.6%, 2.0%, 2.4%, 2.8% or 3%) of the mass of the fluorinated gypsum, and the amount of the composite activator is 1%-3% (for example, 1%, 1.4%, 1.8%, 2.3%, 2.7% or 3%) of the total mass of the cementitious base material; the composite activator comprises sodium sulfate and / or sodium silicate.

[0042] Preferably, in a preferred embodiment of the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention, the cementitious base material comprises, by mass percentage: 60%-65% (e.g., 60%, 61%, 62%, 63%, 64% or 65%) of fluorinated gypsum, 20% of low-calcium fly ash and 20%-25% (e.g., 20%, 21%, 22%, 23%, 24% or 25%) of slag powder; the admixture comprises an alkaline material and a composite activator, The amount of alkaline material is 1.2%-3% of the mass of fluorgypsum, and the amount of composite activator is 2%-3% of the total mass of the cementitious matrix (for example, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%); the composite activator includes sodium sulfate and sodium silicate, and the mass ratio of sodium silicate to sodium sulfate is 1:3-2:1 (for example, 1:3, 1:2.5, 1:2, 1:1.5, 1:1, 1.5:1 or 2:1).

[0043] In a preferred embodiment of the sulfur-alkali dual-excitation solid waste-based cementitious material of the present invention, the cementitious base material comprises, by mass percentage, 60%-65% (e.g., 60%, 61%, 62%, 63%, 64% or 65%) of fluorinated gypsum, 15%-25% (e.g., 15%, 17%, 19%, 21%, 23% or 25%) of low-calcium fly ash and 15%-25% (e.g., 15%, 17%, 19%, 21%, 23% or 25%) of slag powder; the admixture comprises an alkaline material and a composite excitation The amount of alkaline material is 1.0%-3% (for example, 1%, 1.5%, 2%, 2.5% or 3%) of the mass of fluorgypsum, the amount of composite activator is 2%-3% (for example, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%) of the total mass of the cementitious substrate, the composite activator includes sodium sulfate and sodium silicate, and the mass ratio of sodium silicate to sodium sulfate is 1:1-1:2 (for example, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8 or 1:2).

[0044] In the preferred embodiment of the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention, the cementitious base material includes, by mass percentage, 60% fluorgypsum, 15% low-calcium fly ash and 25% slag powder; the admixture includes an alkaline material and a composite activator, the amount of the alkaline material is 1.2% of the mass of the fluorgypsum, the amount of the composite activator is 1.8%-2% of the total mass of the cementitious base material, and the composite activator is sodium sulfate and / or sodium silicate. The selection of the dosage ratio of the above-mentioned raw materials helps to make the 28d compressive strength of the prepared sulfur-alkali dual-activated solid waste-based cementitious material reach a level that is basically equivalent to or even far higher than that of cement, and the 28d softening coefficient can reach more than 0.85, and the water resistance is good.

[0045] Preferably, in terms of mass percentage, the cementitious base material comprises: 60% fluorgypsum, 15% low-calcium fly ash and 25% slag powder; the admixture comprises an alkaline material and a composite activator, the amount of the alkaline material is 1.2% of the mass of the fluorgypsum, the amount of the composite activator is 1.8%-2% of the total mass of the cementitious base material, and the composite activator is sodium sulfate or a mixture of sodium sulfate and sodium silicate (when the composite activator is a mixture of sodium sulfate and sodium silicate, the mass ratio of sodium silicate to sodium sulfate is 1:1-1:3; for example, the mass ratio of sodium silicate to sodium sulfate is 1:1, 1:1.5, 1:2, 1:2.5 or 1:3). The selection of the dosage ratio of the above raw materials helps to make the 28d compressive strength of the prepared sulfur-alkali dual-activated solid waste-based cementitious material reach above 53MPa, and the 28d softening coefficient can reach above 0.85, and the water resistance is good. The raw materials of the sulfur-alkali dual-excitation solid waste-based products of the embodiments of the present invention include the sulfur-alkali dual-excitation solid waste-based cementitious material and water as described above; the mass ratio of water to the sulfur-alkali dual-excitation solid waste-based cementitious material is 0.35-0.45 (for example, 0.35, 0.37, 0.39, 0.41, 0.43, 0.44 or 0.45).

[0046] The present invention also proposes a method for preparing the sulfur-alkali dual-stimulation solid waste-based product as described above, comprising the following steps: S1, weighing water, mixing at least part of the water with a composite activator to fully dissolve the composite activator, and obtaining a composite activator solution; S2, weighing fluorinated gypsum, low-calcium fly ash, slag powder and alkaline materials in proportion, pouring them into a mortar mixer, stirring and mixing them evenly, and obtaining a mixed dry material; S3, adding the composite activator solution obtained in step S1 and water into the mixed dry material, stirring and mixing them evenly, and obtaining a mixed slurry;

[0047] S4. Pour the mixed slurry into a mold, vibrate it thoroughly to make it dense, and after molding and demolding, put it into a standard cement mortar curing box with a temperature of 20°C ± 1°C and a humidity of ≥ 95% for curing (when curing in a high humidity environment with a humidity of ≥ 95%, dihydrate gypsum is easily dissolved in a humid environment, that is, the dihydrate gypsum originally used as the first strength skeleton will dissolve in the saturated pore solution, and then the density and strength will decrease; therefore, under high humidity curing conditions, higher requirements will be placed on the present cementitious material), and the sulfur-alkali dual-excitation solid waste-based product of the present invention will be obtained.

[0048] In a preferred embodiment of the method for preparing the sulfur-alkali dual-stimulation solid waste-based product of the present invention, the amount of water in the composite activator solution is 50% of the total amount of water; when preparing the composite activator solution, the water and the composite activator can be mixed and then left to stand for 24 hours to allow the composite activator to fully dissolve; in step S2, the stirring time can be 1 minute (enough to achieve uniform mixing of the mixed dry materials); in step S3, the composite activator solution and the mixed dry materials can be mixed first, and then the remaining water can be poured into the container containing the composite activator solution and shaken thoroughly before being poured into the mixed dry materials; in step A3, the stirring and mixing time can be 2-4 minutes.

[0049] The sulfur-alkali dual-excitation solid waste-based gelling material, product and preparation method thereof of the present invention are described in detail below through specific embodiments.

[0050] Sources of the raw materials used in the following examples: sodium sulfate, analytical grade, purchased from Tianjin Kemeiou Chemical Reagent Co., Ltd.; sodium silicate (solid, modulus 1), analytical grade, purchased from Tianjin Kemeiou Chemical Reagent Co., Ltd.; calcium oxide, analytical grade, purchased from Tianjin Kemeiou Chemical Reagent Co., Ltd.; high calcium fly ash, purchased from Yantai Anda Environmental Protection Technology Co., Ltd.;

[0051] In the following examples and comparative examples, the compositions of the fluorinated gypsum (pH 4.2), low-calcium fly ash (low-calcium fly ash refers to Class II F fly ash classified according to GB / T 1596-2017), high-calcium fly ash (high-calcium fly ash refers to Class II C fly ash classified according to GB / T1596-2017), carbide slag and slag powder used are shown in Table 1 below:

[0052] Table 1 Main chemical composition of raw materials

[0053]

[0054] In the following embodiments or comparative examples: the amount of alkaline material (calcium oxide or carbide slag) in the admixture is calculated based on the mass of fluorgypsum (the amount of alkaline material given below is the percentage of the mass of alkaline material to fluorgypsum), and the amount of composite activator (sodium sulfate and / or sodium silicate) is calculated based on the total mass of the cementitious base material (the amount of composite activator given below is the percentage of each component in the composite activator to the total mass of the cementitious base material).

[0055] Example 1

[0056] The sulfur-alkali dual-activated solid waste-based gelling material of this embodiment includes a gelling base material and an admixture;

[0057] The cementitious base material comprises, by mass percentage, 60% of fluorgypsum, 15% of low-calcium fly ash and 25% of slag powder;

[0058] Specifically, the admixtures can be:

[0059] S1, calcium oxide 1.2% (1.2% of the mass of fluorgypsum) and sodium sulfate 2% (2% of the total mass of the cementitious base material);

[0060] S2: 1.2% calcium oxide, 0.5% sodium silicate and 1.5% sodium sulfate;

[0061] S3: calcium oxide 1.2%, sodium silicate 1% and sodium sulfate 1%;

[0062] S4: 1.2% calcium oxide, 1.5% sodium silicate and 0.5% sodium sulfate;

[0063] S5: calcium oxide 1.2%, sodium silicate 2%;

[0064] S6: 1.2% carbide slag, 1.0% sodium silicate and 1.0% sodium sulfate;

[0065] The raw materials of the sulfur-alkali dual-excitation solid waste-based product of this embodiment include the sulfur-alkali dual-excitation solid waste-based gelling material and water as described above, and the mass ratio of water to the sulfur-alkali dual-excitation solid waste-based gelling material is 0.35.

[0066] The method for preparing the sulfur-alkali dual-excitation solid waste-based product of this embodiment comprises the following steps:

[0067] S1. Weigh water according to the set ratio of water-binder ratio, take out half of the weighed water, dissolve the composite activator (calcium sulfate and / or calcium silicate) into solution A, and let solution A stand for 24 hours to fully dissolve solution A; the remaining water is solution B;

[0068] S2. Weigh fluorgypsum, fly ash, slag powder and alkaline material (calcium oxide) in proportion, pour into a mortar mixer, stir slowly for 1 minute to mix evenly, and obtain a mixed dry material;

[0069] S3, adding solution A and solution B into the mixed dry material, stirring and mixing evenly to obtain a mixed slurry;

[0070] S4. Pour the mixed slurry into a 40×40×40mm mold, fully vibrate and compact it, and after molding and demoulding, put it into a standard cement mortar curing box with a temperature of 20°C±1°C and a humidity of ≥95% for curing. After the curing is completed, the sulfur-alkali dual-excitation solid waste-based product of this embodiment is obtained.

[0071] Example 2

[0072] The sulfur-alkali dual-activated solid waste-based gelling material of this embodiment includes a gelling base material and an admixture;

[0073] The cementitious base material comprises, by mass percentage, 60% of fluorgypsum, 20% of low-calcium fly ash and 20% of slag powder;

[0074] There are many kinds of admixtures, which are:

[0075] M1: 1.2% calcium oxide, 1% sodium silicate and 1% sodium sulfate;

[0076] M2: 1.5% calcium oxide, 2% sodium silicate and 1% sodium sulfate;

[0077] M3: Calcium oxide 2.5%, sodium silicate 2% and sodium sulfate 1%;

[0078] M4: calcium oxide 1.2%, sodium silicate 1%;

[0079] M5: calcium oxide 1%, sodium silicate 1% and sodium sulfate 1%;

[0080] The raw materials of the sulfur-alkali dual-excitation solid waste-based product of this embodiment include the sulfur-alkali dual-excitation solid waste-based gelling material of this embodiment and water, and the mass ratio of water to the sulfur-alkali dual-excitation solid waste-based gelling material is 0.35.

[0081] The preparation method of the sulfur-alkali dual-excitation solid waste-based product of this embodiment refers to Example 1.

[0082] Example 3

[0083] The sulfur-alkali dual-activated solid waste-based gelling material of this embodiment includes a gelling base material and an admixture;

[0084] The cementitious base material comprises, by mass percentage, 65% of fluorgypsum, 20% of low-calcium fly ash and 15% of slag powder;

[0085] There are many kinds of admixtures, which are:

[0086] N1: calcium oxide 1%, sodium silicate 1% and sodium sulfate 1%;

[0087] N2: 1.2% calcium oxide, 1% sodium silicate and 1% sodium sulfate;

[0088] N3: Calcium oxide 2%, sodium silicate 1% and sodium sulfate 1%;

[0089] N4: 3% calcium oxide, 1% sodium silicate and 1% sodium sulfate;

[0090] The raw materials of the sulfur-alkali dual-excitation solid waste-based product of this embodiment include the sulfur-alkali dual-excitation solid waste-based gelling material of this embodiment and water, and the mass ratio of water to the sulfur-alkali dual-excitation solid waste-based gelling material is 0.35.

[0091] The preparation method of the sulfur-alkali dual-excitation solid waste-based product of this embodiment refers to Example 1.

[0092] Example 4

[0093] The sulfur-alkali dual-activated solid waste-based gelling material of this embodiment includes a gelling base material and an admixture;

[0094] The cementitious base material comprises, by mass percentage, 70% of fluorgypsum, 20% of low-calcium fly ash and 10% of slag powder;

[0095] The additives in this embodiment include: 1.2% calcium oxide, 1% sodium silicate and 1% sodium sulfate.

[0096] Comparative Example 1

[0097] The difference between this comparative example and the sample with S3 as the admixture in Example 1 is that an equal amount of cement (P.O42.5 ordinary Portland cement) is used to replace low-calcium fly ash; the rest is consistent with the sample with S3 as the admixture in Example 1.

[0098] Comparative Example 2

[0099] The difference between this comparative example and the sample with S3 as the admixture in Example 1 is that an equal amount of high-calcium fly ash is used to replace low-calcium fly ash; the rest is consistent with the sample with S3 as the admixture in Example 1.

[0100] Comparative Example 3

[0101] The difference between this comparative example and the sample in Example 1 with the admixture of S3 is only that the usage ratio of low-calcium fly ash and slag powder is different; the rest is consistent with the sample in Example 1 with the admixture of S3.

[0102] In the cementitious base material of this comparative example, the dosage of fluorgypsum is 60%, and the dosage ratios of low-calcium fly ash and slag powder are respectively:

[0103] B1: slag powder 40%;

[0104] B2: low calcium fly ash 40%;

[0105] B3: 25% low calcium fly ash, 15% slag powder;

[0106] B4: 10% low calcium fly ash, 30% slag powder;

[0107] B5: 30% low calcium fly ash, 10% slag powder;

[0108] B6: 5% low calcium fly ash, 35% slag powder;

[0109] B7: 35% low calcium fly ash, 5% slag powder.

[0110] Comparative Example 4

[0111] The difference between this comparative example and the sample in Example 1 in which the admixture is S3 is only that the usage ratio of each raw material in the cementitious base material is different; the rest is consistent with the sample in Example 1 in which the admixture is S3.

[0112] The cementitious base material of this comparative example comprises: 71% of fluorgypsum, 0% of low-calcium fly ash and 29% of slag powder.

[0113] Comparative Example 5

[0114] The difference between this comparative example and the sample with S3 as the admixture in Example 1 is that an equal amount of cement (P·O42.5 ordinary Portland cement) is used to replace slag powder; the rest is consistent with the sample with S3 as the admixture in Example 1.

[0115] Comparative Example 6

[0116] In the fluorinated gypsum-based cementitious material of this comparative example, the cementitious base material is all fluorinated gypsum (100% fluorinated gypsum); the admixtures include 1% calcium oxide and 1% sodium silicate; and the preparation method is the same as that of Example 1.

[0117] Comparative Example 7

[0118] In the fluorinated gypsum-based cementitious material of this comparative example, the cementitious base material is all fluorinated gypsum (100% fluorinated gypsum); the admixtures include 1% calcium oxide, 1% sodium sulfate and 1% sodium silicate; and the preparation method is the same as that of Example 1.

[0119] Comparative Example 8

[0120] The difference between this comparative example and the sample in Example 1 in which the admixture is S3 is only that the amount of sodium silicate and sodium sulfate used is 2% of the total amount of the cementitious base material (that is, the amount of the composite activator used is 4% of the total amount of the cementitious base material); the rest is consistent with the sample in Example 1 in which the admixture is S3.

[0121] Comparative Example 9

[0122] The difference between this comparative example and the sample in Example 1 in which the admixture is S3 is that the composite additive is omitted (ie, the dosage of sodium silicate and sodium sulfate is both 0); the rest is consistent with the sample in Example 1 in which the admixture is S3.

[0123] Comparative Example 10

[0124] The difference between this comparative example and Example 2 is only that:

[0125] The admixtures include: 1% calcium oxide and 1% sodium silicate; the rest are the same as in Example 2.

[0126] Comparative Example 11

[0127] The difference between this comparative example and the sample in Example 2 in which the admixture is M2 is that calcium oxide is omitted (ie, the admixture only includes 2% sodium silicate and 1% sodium sulfate); the rest is consistent with Example 2.

[0128] Comparative Example 12

[0129] The difference between this comparative example and Example 3 is that the admixture is different; the rest is consistent with Example 3.

[0130] The admixtures in this comparative example are:

[0131] N1': calcium oxide 1% and sodium silicate 1%;

[0132] N2': calcium oxide 1.2% and sodium silicate 1%.

[0133] Comparative Example 13

[0134] The difference between this comparative example and Example 4 is that the admixture is different; the rest is consistent with Example 4.

[0135] The admixtures in this comparative example are:

[0136] P1': calcium oxide 1% and sodium silicate 1%;

[0137] P2': calcium oxide 1.2% and sodium silicate 1%;

[0138] P3': calcium oxide 1%, sodium sulfate 1% and sodium silicate 1%.

[0139] Experimental example

[0140] 1. The mixed slurry obtained by the treatment of step S3 for Examples 1-4 and Comparative Examples 1-11 was injected into a triple mold with a size of 40 mm × 40 mm × 40 mm for molding, and the film was sealed and placed in a curing room. After curing for 24 hours under high humidity conditions of 20±2°C and relative humidity ≥95%, the mold was removed, and the samples were cured to an age of 7d and 28d before being taken out. Finally, a press was used to test the compressive strength and softening coefficient of the test blocks (the softening coefficient was tested immediately after the saturation was completed to avoid the recrystallization of dihydrate gypsum in the pore solution due to water loss, which would make the softening coefficient obtained by the test falsely high; softening coefficient = saturated strength / fully dry strength), and the water absorption of some test blocks was tested.

[0141] Compressive strength test method: After the test block reaches the corresponding age, use a compression testing machine to measure the strength of the hardened material at different ages, and take the average of the three groups of results for each group of test pieces to obtain the compressive strength of the final test piece.

[0142] Softening coefficient test method: The softening coefficient (k) represents the ratio of wet compressive strength to dry compressive strength. The compressive strength is divided into dry compressive strength and wet compressive strength. Dry compressive strength measurement: Place the sample in an oven at 45±5℃ and dry it to constant weight for testing; Wet compressive strength measurement: Soak the sample in water for 24 hours to saturate it with water, and gently wipe off the surface moisture with a towel before testing. During the curing process, at least three samples of each sample are measured. The softening coefficient can be used to evaluate the water resistance of samples. For example, the softening coefficient requirement for H0 type moisture-proof gypsum blocks in the JCT698-2010 gypsum block industry standard is ≥0.8; according to the "Uniform Technical Specifications for the Application of Wall Materials" GB 50574-2010, the softening coefficient of block materials should not be less than 0.85; for masonry structures with a design service life of 50 years, the carbonization coefficient and softening coefficient of the block materials should not be less than 0.85, and materials with a softening coefficient less than 0.9 shall not be used for load-bearing walls in humid environments, freeze-thaw environments, and chemical corrosion environments.

[0143] Water absorption rate: The water absorption rate is the difference between the saturated sample and the absolutely dry sample, divided by the weight of the absolutely dry sample. It is used to indicate the difficulty of water penetration, and can also indirectly characterize the size of the connected porosity in the sample. Generally speaking, the lower the water absorption rate, the more difficult it is for water to penetrate, and the lower the connected porosity.

[0144] The test results are shown in Table 2-5 and Figure 1-2 As shown:

[0145] Table 2 Compressive strength, softening coefficient and water absorption of the test blocks obtained in Example 1 and Comparative Examples 1-9

[0146]

[0147]

[0148] Table 3 Compressive strength, softening coefficient and water absorption of the test blocks obtained in Example 2 and Comparative Examples 10-11

[0149]

[0150] Table 4 Compressive strength, softening coefficient and water absorption of the test blocks obtained in Example 3 and Comparative Example 12

[0151]

[0152] Table 5 Compressive strength, softening coefficient and water absorption of the test blocks obtained in Example 4 and Comparative Example 13

[0153]

[0154] Experimental results analysis:

[0155] (1) In combination with Tables 2-5 above, it can be seen that the 28d softening coefficient of the sulfur-alkali dual-excitation solid waste-based cementitious materials of Examples 1-4 is greater than 0.85 (important buildings or structures that are in water or humid environments for a long time must use materials with a softening coefficient greater than 0.85; for materials used for less humid or secondary structures, the softening coefficient must not be less than 0.75; it is generally believed that materials with a softening coefficient greater than 0.85 are water-resistant materials), and have good water resistance; and the 28d compressive strength of the sulfur-alkali dual-excitation solid waste-based cementitious materials of Examples 1-4 is greater than 30MPa, and has good mechanical properties. In addition, during the high humidity curing process, the softening coefficient and compressive strength of the sulfur-alkali dual-excitation solid waste-based cementitious materials of Examples 1-4 both show an increasing trend, indicating that the sulfur-alkali dual-excitation solid waste-based cementitious materials of the present invention will not experience a reduction in water resistance and mechanical properties during the high humidity curing process. The compressive strength and water resistance coefficient of the test block show a continuous growth trend with the increase of curing age. This is because the composite excitation in the early stage promoted the concentration change of silicate ions and sulfate ions in the system, stimulated the dissolution-crystallization process of slag powder and anhydrous gypsum, promoted the early hydration, and obtained a certain strength and water resistance. With the development of the hydration process, the system becomes more and more dense, and the generated water-resistant hydration products are gradually wrapped on the gypsum surface, and the strength and softening coefficient also increase accordingly.

[0156] Furthermore, the 7d softening coefficients of the sulfur-alkali dual-activated solid waste-based cementitious materials of Examples 1-3 are all around 0.75, and they have good water resistance when cured at high humidity for 7 days.

[0157] Furthermore, the 7d softening coefficient of the sulfur-alkali dual-activated solid waste-based cementitious material in Example 1 with the admixtures S1, S3, S5 and S6 and the sulfur-alkali dual-activated solid waste-based cementitious material in Example 2 with the admixture M3 is greater than 0.85, and with the extension of the curing time, both the softening coefficient and the compressive strength are increased, which can achieve the continuous development of strength and water resistance in a high humidity environment.

[0158] (2) Combining the sample in Example 1 with the admixture of S3 and the sample in Comparative Example 1 in Table 2, it can be seen that when low-calcium fly ash is replaced with cement, the softening coefficients at 7d and 28d are significantly reduced, and the 28d compressive strength is also significantly reduced, indicating that low-calcium fly ash is more suitable for the present invention than cement. In addition, the cost of low-calcium fly ash is also significantly lower.

[0159] Combining the samples in Example 1 in Table 2 with the admixture S3 and the samples in Comparative Example 2, it can be seen that: when the low-calcium fly ash is replaced by the high-calcium fly ash, the 28d softening coefficient and compressive strength are significantly reduced, and the 28d softening coefficient is reduced to below 0.85; this shows that the high-calcium fly ash cannot play the same role as the low-calcium fly ash in the present invention, and the low-calcium fly ash can play a significantly better role in ensuring the 28d water resistance coefficient and improving the water resistance (the low-calcium fly ash in the present invention can play the role of a baton in developing the later compressive strength and water resistance in the later stage of curing, and maintain the stability of the performance of the cementitious material under the later high-humidity curing conditions).

[0160] Combining the sample with the admixture S3 in Example 1 and the sample in Comparative Example 3 in Table 2, it can be seen that the dosage ratio of low-calcium fly ash and slag powder will have a significant impact on the softening coefficient or compressive strength of the sulfur-alkali dual-excitation solid waste-based cementitious material of the present invention; if the dosage ratio of low-calcium fly ash and slag powder is not appropriate, the softening coefficient at 28d will even be lower than 0.85, and the softening coefficient and / or compressive strength will shrink during high humidity curing. Among them, when low-calcium fly ash is omitted (the dosage of slag powder is 40%; that is, B1 in Comparative Example 3), although the compressive strength and softening coefficient are both high, the compressive strength and softening coefficient develop slowly during the curing process under high humidity conditions, and the cost of slag powder is significantly higher than that of low-calcium fly ash (the cost of slag powder is about 350 yuan / ton, and the cost of low-calcium fly ash is about 120 yuan / ton), and the economic benefits are poor.

[0161] Combining the sample in Example 1 in Table 2 in which the admixture is S3 and the sample in Comparative Example 4, it can be seen that: when the amount of fluorgypsum is greater than 70% and low-calcium fly ash is omitted in the cementitious base material (the cementitious base material only includes fluorgypsum and slag powder), as the curing time increases, the softening coefficient shrinks (the 28d softening coefficient is less than the 7d softening coefficient, and the 28d softening coefficient is less than 0.85), and the water resistance is poor; and the 28d compressive strength of Comparative Example 4 is also significantly lower.

[0162] Combining the sample in Example 1 in Table 2 with the admixture S3 and the sample in Comparative Example 5, it can be seen that if the slag powder is replaced with an equal amount of cement, as the curing time increases, the softening coefficient shrinks (the 28d softening coefficient is less than the 7d softening coefficient, and the 28d softening coefficient is less than 0.85), and the water resistance is poor; and the 28d compressive strength of Comparative Example 5 is also significantly lower.

[0163] Combining the samples of Example 1 in Table 2 with the admixture S3 and the samples of Comparative Examples 6-7, it can be seen that when the cementitious base material is entirely made of fluorinated gypsum, the 28d compressive strength and softening coefficient are significantly lower (the 28d softening coefficient is less than 0.85).

[0164] Combining the sample in Example 1 with the additive S3 and the sample in Comparative Example 8 in Table 2, it can be seen that when the dosage of the composite activator is 4%, the softening coefficient will shrink.

[0165] Combining the sample in Example 1 in Table 2 with the admixture S3 and the sample in Comparative Example 9, it can be seen that if the composite activator is omitted, the compressive strength will be significantly reduced.

[0166] (3) Combined with Table 3, it can be seen that the performance of the cementitious material is better when the amount of alkaline material is 1.2%-2.5%, the amount of composite activator is 2%-3%, and the mass ratio of sodium silicate to sodium sulfate in the composite activator is 1:1-2:1; in addition, when the amount of alkaline material is greater than 1.5%, it will have a certain adverse effect on the compressive strength of the cementitious material.

[0167] (4) In combination with Table 4, it can be seen that when the cementitious base material includes 65% fluorgypsum, 20% low-calcium fly ash and 15% slag powder, the appropriate amount of alkaline material is 1%-3% (1.2% is optimal), and a composite activator containing both sodium silicate and sodium sulfate is used (for example, the mass ratio of sodium silicate to sodium sulfate is 1:1).

[0168] (5) In combination with Table 5, it can be seen that when the cementitious base material includes 70% fluorgypsum, 20% low-calcium fly ash and 10% slag powder, the appropriate amount of alkaline material is greater than 1% (for example, 1.2%), and a composite activator containing both sodium silicate and sodium sulfate is used (for example, the mass ratio of sodium silicate to sodium sulfate is 1:1).

[0169] 2. The sulfur-alkali dual-excitation solid waste-based products cured for 7 days and 28 days in Example 3 were observed under a high-magnification (5000×) scanning electron microscope.

[0170] Test method: The strength of the pure paste is measured at a predetermined age. The corresponding paste is crushed at the same age and then soaked in anhydrous alcohol for 48 hours to stop its further hydration. The sample fragments are dried at 60°C and observed by SEM scanning electron microscope.

[0171] The high-power (5000×) scanning electron microscope image after curing for 7 days is as follows Figure 3 As shown. Figure 3 It can be seen that the anhydrous spherical gypsum crystals in the middle have been partially hydrated into plate-columnar dihydrate gypsum crystals, and the first strength skeleton is being formed. The C-(A)-SH gel and slender oblique strip-shaped ettringite crystals are being generated below the two sides, and in the high sulfate environment, the transformation of ettringite (AFt) to low-strength monosulfate (AFm) is prevented. This reflects the key to improving the strength and water resistance of the system.

[0172] The high-power (5000×) scanning electron microscope image after curing for 28 days is as follows Figure 4As shown. Figure 4 It can be seen that most of the anhydrous spherical gypsum crystals are hydrated into thick plate-like dihydrate gypsum crystals, with only a small part remaining unhydrated. In the hydration process, the C-(A)-SH gel and the dihydrate gypsum crystals are increasingly cross-linked, the calcium aluminate crystals are wrapped by the C-(A)-SH gel, and various hydration products overlap and cross-link together, which is the key to the increasing strength and water resistance coefficient.

[0173] In summary, in the sulfur-alkali dual-activated solid waste-based cementitious material of the present invention, both slag powder and low-calcium fly ash contain rich Si and Al components, and the Ca provided by fluorinated gypsum 2+ With SO4 2- , through the composite excitation of the alkaline activator and the alkaline material, the composition of the early hydration product changes from a single dihydrate gypsum to a double-support skeleton structure mainly composed of "dihydrate gypsum-C-(A)-SH gel and Aft" (the relative hydration rates of fluorinated gypsum, slag powder and low-calcium fly ash have an important influence on the formation of the double-support skeleton structure), which hinders the direct contact between water molecules and dihydrate gypsum crystals; the hydration product becomes richer, the overlap is denser, and the strength and water resistance coefficient and other properties are excellent and continuously improved throughout the whole age period); low-calcium fly ash is mainly responsible for the stability of the later system in the present invention, and its hydration is very slow. In the early stage, due to its particle fineness, the early density is improved. In the later stage, it is continuously hydrated and consumes calcium hydroxide to generate Aft and C-(A)-SH gel, which ensures the continuous development of the later strength and softening coefficient, and achieves the effect of high strength and high water resistance throughout the whole age period. The above description is only a preferred embodiment of the present invention and is not used to limit the present invention. For those skilled in the art, the present invention can have various modifications and changes. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Sulfur-alkali dual-excitation solid waste-based cementitious material, characterized in that: The sulfur-alkali dual-excitation solid waste-based gelling material comprises a gelling base material and an admixture; Calculated by mass percentage, the cementitious base material comprises: 60%-70% fluorgypsum, 15%-25% low-calcium fly ash and 15%-25% slag powder; The admixture comprises an alkaline material and a composite activator, wherein the amount of the alkaline material is 1%-3% of the mass of the fluorinated gypsum, and the amount of the composite activator is 0.5%-3% of the total mass of the gelling base material; The composite activator includes sodium sulfate and / or sodium silicate.

2. The sulfur-alkali dual-excitation solid waste-based gelling material according to claim 1, characterized in that: The alkaline material is calcium oxide and / or carbide slag, and the amount of the alkaline material is 1.2%-2.5% of the mass of the fluorgypsum.

3. The sulfur-alkali dual-excitation solid waste-based gelling material according to claim 1, characterized in that: The composite activator is composed of sodium sulfate and sodium silicate. The amount of the composite activator is 1.8%-3% of the total mass of the gelling substrate. The mass ratio of the sodium silicate to sodium sulfate is 1:3-2:

1.

4. The sulfur-alkali dual-excitation solid waste-based cementitious material according to any one of claims 1 to 3, characterized in that: The mass ratio of the low-calcium fly ash to the slag powder is 0.6-1.

3.

5. The sulfur-alkali dual-excitation solid waste-based gelling material according to claim 4, characterized in that: The mass ratio of the low-calcium fly ash to the slag powder is 0.6-1.

6. The sulfur-alkali dual-excitation solid waste-based cementitious material according to claim 1, characterized in that: Calculated by mass percentage, the cementitious base material includes: 60% fluorgypsum, 15% low-calcium fly ash and 25% slag powder; the admixtures include alkaline materials and composite activators, the amount of alkaline materials is 1.2% of the mass of fluorgypsum, the amount of composite activators is 1.8%-2% of the total mass of the cementitious base material, and the composite activators are sodium sulfate and / or sodium silicate.

7. A sulfur-alkali dual-excitation solid waste-based product, characterized in that: The raw materials of the sulfur-alkali dual-excitation solid waste-based product include the sulfur-alkali dual-excitation solid waste-based gelling material according to any one of claims 1 to 6 and water; The mass ratio of water to the sulfur-alkali dual-excitation solid waste-based gelling material is 0.35-0.

45.

8. The method for preparing the sulfur-alkali dual-excitation solid waste-based product according to claim 7, characterized in that: The steps include: S1, weighing water, mixing at least part of the water with the composite activator to fully dissolve the composite activator, and obtaining a composite activator solution; S2, weighing the fluorinated gypsum, low-calcium fly ash, slag powder and alkaline material in proportion, pouring them into a mortar mixer, stirring and mixing them evenly to obtain a mixed dry material; S3, adding the composite activator solution and water obtained in step S1 into the mixed dry material, stirring and mixing evenly to obtain a mixed slurry; S4. Pour the mixed slurry into a mold, fully vibrate and compact it, and after molding and demoulding, put it into a standard cement mortar curing box for curing to obtain the sulfur-alkali dual-activated solid waste-based product.

9. The method for preparing the sulfur-alkali dual-excitation solid waste-based product according to claim 7, characterized in that: In step S4, the curing temperature is 20°C ± 1°C, and the curing humidity is ≥ 95%.

Citation Information

Patent Citations

  • High-water-resistance gypsum-based cementing material and preparation method thereof

    CN118324481A

Cited By

  • Solid waste-based cementitious material, preparation method and application thereof

    CN122685365A